2000
DOI: 10.1164/ajrccm.162.5.2001040
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Age-related Changes in Pulmonary Tuberculosis Images and the Effect of Diabetes

Abstract: Atypical radiologic images of pulmonary tuberculosis are common in elderly and in diabetic patients. To investigate the relationship of chest radiographic findings of tuberculosis to age in diabetic and nondiabetic patients, we compared the chest radiographic findings of 192 inpatients with pulmonary tuberculosis and diabetes with those of 130 patients with pulmonary tuberculosis alone. The proportion of patients with lower lung field lesions progressively increased with age (r(S) = 0.89, p < 0.01), whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
68
4
7

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 21 publications
12
68
4
7
Order By: Relevance
“…Diabetes mellitus was also found to be strongly associated with advancing age, in accordance with the findings of other authors, (19,20) who include this disease in the list of those which increase the susceptibility to pulmonary tuberculosis, even causing alterations in the usual radiological aspect of the disease, such as involvement of the lower lobes. (5,20,21) The cardiovascular diseases evaluated in the present study were also strongly associated with being elderly, although no causal relation with pulmonary tuberculosis was established. This might be another confounding factor, since such diseases are quite frequently present in any elderly population and not only in that with pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Diabetes mellitus was also found to be strongly associated with advancing age, in accordance with the findings of other authors, (19,20) who include this disease in the list of those which increase the susceptibility to pulmonary tuberculosis, even causing alterations in the usual radiological aspect of the disease, such as involvement of the lower lobes. (5,20,21) The cardiovascular diseases evaluated in the present study were also strongly associated with being elderly, although no causal relation with pulmonary tuberculosis was established. This might be another confounding factor, since such diseases are quite frequently present in any elderly population and not only in that with pulmonary tuberculosis.…”
Section: Discussionsupporting
confidence: 89%
“…(6,15) Within this context, we found that more diseases associated with the elderly, especially diabetes, lung diseases, and cardiovascular diseases, which is in accordance with the findings of other authors. (16)(17)(18)(19)(20) Other lung diseases, present in 38% of the elderly patients with concomitant diseases, might be confounding factors in the diagnosis of pulmonary tuberculosis, since they present similar symptoms. Diabetes mellitus was also found to be strongly associated with advancing age, in accordance with the findings of other authors, (19,20) who include this disease in the list of those which increase the susceptibility to pulmonary tuberculosis, even causing alterations in the usual radiological aspect of the disease, such as involvement of the lower lobes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there have been studies in which the symptomatic period did not differ among age brackets but did differ in relation to radiological findings. (25,26) In the present study, there was no difference between the two groups in terms of the infiltrates and cavitations seen on chest X-rays. Therefore, we can conclude that, radiologically, suspicion of the disease in the sample observed was possible in the two groups, and no atypical radiological forms (lesions in lower lobes, masses, atelectasis, etc.)…”
Section: Discussioncontrasting
confidence: 55%
“…(21) One group of authors also described the atypical presentation of pulmonary TB in patients with diabetes. (22) Among the patients with diabetes included in our study, a history of weight loss was less common. However, there was not a higher prevalence of other unusual clinical and radiological changes in this group.…”
Section: Discussionmentioning
confidence: 94%